INTERFAITH MARRIAGE FROM A LEGAL PERSPECTIVE INDONESIA AND THAILAND: BETWEEN REGULATION AND FREEDOM OF RELIGION - Pratiwi, Dea; Rahmi, Atikah (International Journal of Cultural and Social Science, 2026)
Interfaith marriage is a social phenomenon that continues to grow in multicultural societies, but still raises legal debates regarding legal certainty and freedom of religion. This article aims to analyze the implementation of legal norms regarding interfaith marriage in social and institutional practices in Indonesia and Thailand, as well as to assess the extent to which legal regulations in both countries reflect a balance between legal certainty and freedom of religion. This study uses a normative legal research method with a regulatory, conceptual, and comparative approach. Data was obtained through a literature study of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively. The results of the study show that in Indonesia, interfaith marriages face significant legal obstacles because the marriage law system still uses religion as the basis for the validity of marriage, as stipulated in Law Number 1 of 1974. This condition creates legal uncertainty and encourages couples to pursue alternative strategies, such as applying for a court ruling or getting married abroad. In contrast, Thailand implements a more secular and administrative marriage law system, where the validity of marriage is determined through civil registration without requiring religious similarity, although in Muslim communities the role of the Islamic Religious Council remains influential socially and religiously. This study concludes that the regulation of interfaith marriage in Thailand is relatively more capable of balancing legal certainty and religious freedom compared to Indonesia. Therefore, it is necessary to reformulate marriage law policies in Indonesia to be more adaptive and inclusive in order to respond to the social reality of a pluralistic society without neglecting constitutional and social values.